FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI WILAYAH PUSKESMAS SEBA KABUPATEN SABU RAIJUA TAHUN 2022 - Ninda Ayu Lestari Ully; Agus Setyobudi; Ribka Limbu (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
At the Seba Health Center, the prevalence of cases of hypertension was 15,1% in 2019; this number rose to 18,9% in 2021. The goal of this study was to examine the variables influencingi the prevalence of hypertension in elderly people in the Seba Health Center neighborhood of the Sabu Raijua Regency in 2022. Analyticali observationali studyi with a case-control studyi designis the sort of research being done. Throughout the months of November and December 2022, the study done in the Sabu Raijua Regency's Seba Health Center workplace. Interviews were used to gather data, while documentation and questionnaires were also used. The link between independent factors and the dependent variable was examinedi usingi thei Chi-squarei test.Chi-square test results showed a significant correlation between caffeine intake (p=0.0100.05), obesity (p=0.0180.05), stress (p=0.0350.05), and consumption of fatty foods (p=0.0090.05) . and the prevalence of hypertension in the elderly. While there was no correlation between the incidence of hypertension in the elderly and smoking or alcohol use (p=0.600>0.05), therei wasi a correlationi betweeni thei two (p=0.429>0.05). Accordingi to thei researchi findings, there is no substantial relationship between smoking or alcohol use and the prevalence of hypertension, but there is a strong relationshipi betweeni coffee drinking, obesity, stress, and consumptioni ofi fatty foods with the incidence of hypertension.